The mediating and joint effects of depression in the association between cardiovascular health and frailty in middle-aged and elderly people: evidence from NHANES - Ma, Qiaoli; Zou, Zhijuan; Liu, Yanpeng; Zhang, Lei (Frontiers in Psychiatry, 2025)
ObjectiveThis study investigates the correlation between Life’s Essential 8 (LE8), a cardiovascular health (CVH) metric, and frailty in middle-aged and elderly individuals in the United States, also examining how depression mediates this relationship.MethodsParticipants from the NHANES 2005-2018 were analyzed for correlations between LE8 and frailty, along with the combined effects of LE8 and depression using multiple logistic regression. Dose-response relationships were assessed using restricted cubic splines (RCS), and mediation analysis explored depression’s role. Sensitivity and subgroup analyses were conducted for result stability.ResultsThe study included 8,982 participants, with 3,103 frailty events. A higher LE8 score was significantly associated with a reduced risk of frailty, with adjusted odds ratios for the medium and high CVH groups at 0.49 (95% CI: 0.40-0.58, p < 0.001) and 0.21 (95% CI: 0.13-0.33, p < 0.001), respectively. The RCS model showed a negative dose-response relationship. No significant association was found between LE8 and frailty in the depressed population, where depression mediated 32.13% of the relationship.ConclusionMaintaining good cardiovascular health, as measured by LE8, is key to reducing frailty risk in middle-aged and elderly individuals. This underscores the importance of cardiovascular health assessments and targeted health programs to improve quality of life.